2011
DOI: 10.2139/ssrn.1908128
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Poverty in Developing Countries: A Snapshot from the World Health Survey

Abstract: The association between disability and poverty has been noted intuitively, although there is little systematic evidence to support this claim, mainly due to a lack of quality data on disability. This paper attempts to fill a knowledge gap on disability and poverty in developing countries by using a unique data set, the World Health Survey, which has comparable measures of disability and economic indicators for working age population in 15 developing countries. Disability is significantly associated with higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 50 publications
2
110
0
8
Order By: Relevance
“…Some other equally important areas such as the impact on the psychosocial health were not included'' [20]. In Zimbabwe, the average individual with a disability is seven years older than the average individual without a disability (mean age: 41 versus 31 years) [21]. While rehabilitation services for children are essential, the findings in Rwanda also support the importance of rehabilitation service as part of comprehensive health care for adults and senior citizens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some other equally important areas such as the impact on the psychosocial health were not included'' [20]. In Zimbabwe, the average individual with a disability is seven years older than the average individual without a disability (mean age: 41 versus 31 years) [21]. While rehabilitation services for children are essential, the findings in Rwanda also support the importance of rehabilitation service as part of comprehensive health care for adults and senior citizens.…”
Section: Discussionmentioning
confidence: 99%
“…The 2001 South African census showed that in males and females the prevalence of disability was 5.1% and 5%, respectively [19]. However, in Zimbabwe, disability prevalence for women was higher than that of men (12.9% versus 9%, respectively) [21]. In the latter case, this may be explained by the fact that women are more readily involved in development projects at the community level [22] and therefore more easily reached in surveys of this kind.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among adults, the rural-urban divide was less marked, and the lowest access to support services was in rural highland and rural coastal barangays. World Health Survey data for the working-age Filipinos also identified a higher prevalence of disability in rural areas (Mitra et al, 2011). Fewer employment opportunities and migration of ablebodied adults to urban areas for work (Reichert, Myers, 2014;Marella et al, 2016), would contribute to this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Kısaca, engelli bireye sahip hanelerin yoksul olma olasılıkları yüksek olmakla birlikte yoksulluk düzeyleri de daha yüksek olacaktır. Gelişmiş ülkelerde ise (a) engelli kişinin çalışamayacağı ihtimali (b) engelli kişiye bakım vermek üzere diğer bir aile üyesinin okuldan/işinden ayrılma olasılığı (c) engelli bir aile üyesine sahip hanedeki sağlık bakımı ile diğer müdahale masraflarının, engelli bir aile üyesine sahip olmayan hanedeki aynı masraftan daha yüksek olduğu gerçeği yoksulluğu şiddetlendirmektedir ki buna "özürlülüğün gizli maliyeti" denilir (World Bank, 2005;McClain-Nhlapo, 2007;Groce, Kembhavi, Wirz, ve ark., 2011;Mitra, Posarac ve Vick, 2011).…”
Section: Engellilik Ve Yoksulluk İlişkisiunclassified